252 Comparison of two ultra-staging protocols for the detection of lymph node metastases in early stage cervical and endometrial cancer. (18th September 2019) - Buda, A; Grassi, T; Lamanna, M; De ponti, E; Perego, P; Di Martino, G; Dell'Orto, F; Bazzurini, L; Magni, S; Adorni, M; Paderno, M; Landoni, F
Abstract : Objectives: Ultra-staging (US) of sentinel lymph nodes (SLN) increases the detection of nodal metastases. US protocols vary among gynecologic pathologists, and internationally accepted guidelines are still not available. This study compares two US protocols (US-A vs US-B) in early stage cervical (CC) and endometrial cancers (EC) (table 1). Methods: We retrospectively evaluated patients with clinical stage I endometrial cancer (EC) or stage IA-IB1 cervical cancer (CC) who underwent primary surgery with SLN biopsy from November 2010 to October 2017. Results: 229 patients were analyzed (161 ECs and 68 CCs). The rate of positive node disease was: 22% with US-A protocol and 12% with US-B protocol (p=0.09) for EC patients; 22% and 10% (p=0.18) for CC patients. Macrometastasis, micrometastases, and ITC were 31%, 61% and 8%, respectively with US-A protocol; 43%, 40% and 17%, respectively with US-B protocol (p=0.272). Mean size of nodal metastasis was 5.4±6.3 mm for US-A and 3.2±4.3 mm for US-B protocol (p=0.09). On multivariate analysis including grade and LVSI, the US method was not associated with the detection of nodal metastases. Conclusions: Approximately 50% of the nodal metastases detected by US of SLNs were low-volume metastases. In this study, the detection of positive node disease was not associated with the type of US protocol used. Larger multicenter prospective studies are advisable to confirm these results.